Teacher Reform in Indonesia : The Role of Politics and Evidence in Policy Making - Chang, Mae Chu (Washington, DC: World Bank, 2013)
With close to three million teachers, Indonesia has one of the largest and most diverse cadres of teachers in the world. The evolving nature of its education system and the increasingly complex challenges facing individual teachers and the teaching profession as a whole are of immense importance to the nation’s future development.